3^4
(-2)^3
(-2)^6
0^5
5^0
(^2)^2
(^7)^3
6^-2
(-3/1)^-1
me ajudem pleaseeee
Soluções para a tarefa
Respondido por
1
3^4 = 3.3.3.3 = 81
(-2)^3 = (-2).(-2).(-2)= -8
(-2)^6 =(-2).(-2).(-2).(-2).(-2).(-2) = 64
0^5 =0.0.0.0.0 = 0
(X^2)^2 = X^2.2 = X^4
(X^7)^3 = X^7.3 = X^21
(6)^-2 = (1/6)^2 = 1^2/6^2 = 1.1/6.6 = 1/36
(-3/1)^-1 = (-1/3)
(-2)^3 = (-2).(-2).(-2)= -8
(-2)^6 =(-2).(-2).(-2).(-2).(-2).(-2) = 64
0^5 =0.0.0.0.0 = 0
(X^2)^2 = X^2.2 = X^4
(X^7)^3 = X^7.3 = X^21
(6)^-2 = (1/6)^2 = 1^2/6^2 = 1.1/6.6 = 1/36
(-3/1)^-1 = (-1/3)
auston1:
nao tem calculo?
Perguntas interessantes
Português,
11 meses atrás
Geografia,
11 meses atrás
Português,
11 meses atrás
Ed. Física,
1 ano atrás
Matemática,
1 ano atrás
Geografia,
1 ano atrás